2021
DOI: 10.3390/ijerph18062904
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Hypoxia-Awareness Training to the Familiarization of Personal Symptoms for Occupational Safety in the Flight Environment

Abstract: Hypoxia remains a flight-safety issue in terms of aviation medicine. Hypoxia-awareness training has been used to help aircrew members recognize personal hypoxia symptoms. There is still no study, as yet, to establish the association of within-subject data between inflight hypoxia events and the altitude chamber. The main purpose of our study was to use paired subjects’ data on inflight hypoxia symptoms compared with those experienced during training. A questionnaire was developed to obtain information on milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Previous researches have demonstrated that aircrews of fixed-wing airframes detected ongoing in-flight hypoxia incidents based on the memory of personal hypoxia symptoms and sensations inside the chamber flights [3,4,15,24,25]. Nevertheless, to the best of our knowledge, there are still no studies to investigate the consistent relationship between the altitude hypoxia training and the in-flight hypoxia events for helicopter aircrews.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have demonstrated that aircrews of fixed-wing airframes detected ongoing in-flight hypoxia incidents based on the memory of personal hypoxia symptoms and sensations inside the chamber flights [3,4,15,24,25]. Nevertheless, to the best of our knowledge, there are still no studies to investigate the consistent relationship between the altitude hypoxia training and the in-flight hypoxia events for helicopter aircrews.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the fundamental objectives of physiological training is to promote the recognition of symptoms associated with hypoxia (hot flashes, paresthesia, dizziness, cognitive deficits, and headache) that may appear in real flight conditions due to hypoxic events (for example, an abrupt depressurization) and, thus, decrease accidents. In addition, during the physiological training test in hypoxia, the presence of these symptoms constitutes the primary alert for the evaluating personnel to administer supplemental oxygen [ 10 ].…”
Section: Introductionmentioning
confidence: 99%